PENGGUNAAN ALAT BUKTI REKAMAN VIDEO CLOSED CIRCUIT TELEVISION (CCTV) DALAM TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DIWILAYAH KOTA PEKANBARU - David Hidayat; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The rise of motorcycle theft crimes in big cities like in the city of Pekanbaru requires securitysurveillance that is able to supervise 24 hours such as CCTV, CCTV video recordings are often used toanalyze criminal cases, one of which is motorcycle theft. The police in disclosing the perpetrators ofmotorcycle theft recorded by CCTV seem to be slow in the investigation process, because the police inconducting an investigation after a report or complaint from the injured party. The purpose of this thesis isto find out the use of CCTV video evidence in the disclosure of motor vehicle theft. Second, to find out theobstacles of the police in following up the theft of motor vehicles recorded by CCTV. Third, to find out theproof of CCTV video recordings in proving criminal offenses.This type of research can be classified as sociological research. The research location is PekanbaruPolice Department. Document sources used are primary data and secondary data. Document collectiontechniques are interviews, and library studies. After the data collected is then analyzed qualitatively byusing a deductive method that is drawing conclusions from things that are general to things that arespecific.From the results of the study there are three main things that can be concluded. First, theimplementation of law enforcement uses CCTV in uncovering perpetrators of motorcycle theft perpetrated ina pre-emtive, preventive and repressive manner. Secondly, the obstacles of the police in uncovering theperpetrators of motorcycle theft that were tracked by CCTV where internal and external obstacles werefound. Third, the efforts made by the police in uncovering the perpetrators of motorcycle theft recorded byCCTV are supposed to overcome obstacles both internally and externally.Keywords: Evidence-Use of CCTV footage-Crime-Theft